Effect of the Lifting Velocity and Container Shape on Angle of Repose of Iron Ore Particles - Tongqing Li; Yuxing Peng; Zhencai Zhu; Zhangfa Yu; Zixin Yin (Advances in Materials Science and Engineering)
To investigate the impact of lifting velocity and container shape on angle of repose, the fixed-base cylinder method was performed using three types of container shape. The container shape was lifted a series of lifting velocities. Six size fractions of iron ore particles ranging from coarser to fine particles were used as the test materials. And the sand-pile calibration method was then used to calibrate the contact parameters of iron ore particles. Results show angle of repose decreased exponentially with the lifting velocity, while it appeared approximately to be invariant to particle shape, for all size fractions. The sand pile highly depends on the container shape at a low lifting velocity but appears to be invariant to particle size for a high lifting velocity. And then a predictive equation is established and a very close agreement between the predicted and measured angle of repose is attained. Finally, a series of DEM simulations considering the irregular particle shape are conducted by means of sphere clump method to calibrate the contact parameters and are in good visual agreement with the experimental results, indicating the “tuned” contact parameters as well as the applicability of the predicted equation.